German Bundesliga Clubs' rankings in season 2010/11 were significantly affected by the number of players released to World Cup 2010 - Lames, M.; Kolbinger, O. (International Journal of Performance Analysis in Sport, 2011)
The aim of the study was to analyse the influence of the 2010 World Cup for teams of the German Bundesliga that had to release from up to 13 to no players. For the 34th day of the 2009/10 season and all days of the first round 2010/11 the rankings and the number of World Cup internationals were obtained for every team. Spearman's rank correlations were calculated and compared to the rank correlation of day 34 of the 2009/10 season. Significant differences (p < 0.05) for seven days with medium to strong effect sizes for all seventeen days of the first round were found. These findings prove that rankings of clubs from German Bundesliga were affected considerably by their releases to World Cup. Teams with many releases underperformed in the first half of the season whereas teams with few or no releases performed surprisingly well. These facts may be explained by a lacking or inadequate preparation of the internationals leading to a bad start into the season with only partial recovery until mid-season.